The "Subtle" connection between development of cardiac implantable electrical device infection and survival after complete system removal: An observational prospective multicenter study. (1st January 2018) - Diemberger, Igor; Migliore, Federico; Biffi, Mauro; Cipriani, Alberto; Bertaglia, Emanuele; Lorenzetti, Stefano; Massaro, Giulia; Tanzarella, Gaia; Boriani, Giuseppe
Abstract: Background: Despite the improvements in transvenous lead extraction (TLE), patients with cardiac implantable device related infection (CIEDI) have a poor prognosis at long term. We explored the possible role of factors associated with development of CIEDI as predictors of post-TLE survival. Methods: We performed a multi-center prospective observational study in a population of consecutive patients referred for TLE for CIEDI. We adopted a previously developed 10-point scale for CIEDI risk stratification and assessed its performance in predicting post-TLE survival. Results: We enrolled 169 consecutive patients with CIEDI (systemic infection in 48.5% and vegetations in 24.5%). A Shariff score ≥ 3 was present in 102/169 (60.4%) of the enrolled patients. Complete radiological success of TLE was obtained in 163 patients. Twenty-seven patients (15.9%) died after a mean follow-up of 20.8 ± 12.0 months. Two factors were independently associated with post-TLE death: a Shariff score ≥ 3 (HR 10.833, 95% CI 2.544–46.129; p = 0.001) and the presence of vegetations at transesophageal echocardiography (HR 3.324, 95% CI 1.530–7.221; p = 0.002). Conclusions: Risk factors for development of CIEDI are also predictive of post TLE mortality, together with the presence of vegetations. Improvement of our preventive strategies for CIEDI is crucial for enhancing the outcomes of CIED patients overall.